A polypropylene composite material and its preparation method and application

By combining 1-octene-ethylene block copolymer and ethylene-propylene copolymer in polypropylene materials, combining high-density polyethylene resin and glass fiber, and using specific nucleating agents, the problems of low strength and poor scratch resistance in automotive interior applications are solved, and the material's good appearance and excellent bending and cracking resistance are achieved.

CN117164992BActive Publication Date: 2025-04-18TIANJIN KINGFA NEW MATERIAL +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311251768.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-18
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

The existing polypropylene materials have shortcomings such as low strength, easy to bend, white and crack, and not scratch-resistant in automotive interior applications, which limit their application scope.

Method used

The combination of 1-octene-ethylene block copolymer and ethylene-propylene copolymer is used as toughening agents, combining high-density polyethylene resin and glass fibers, and the toughness and rigidity of the material are improved through the specific nucleation agent ratio, and its bending and cracking resistance and scratch resistance are improved.

Benefits of technology

It realizes the good appearance, excellent bending and cracking resistance and scratch resistance of polypropylene composite materials, and is suitable for the application of automotive interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004470475600000081
    Figure BDA0004470475600000081
  • Figure BDA0004470475600000091
    Figure BDA0004470475600000091
  • Figure BDA0004470475600000092
    Figure BDA0004470475600000092
Patent Text Reader

Abstract

The present invention relates to a polypropylene composite material and a preparation method and application thereof, belonging to the field of automotive interior and exterior materials. The glass fiber reinforced polypropylene composite material of the present invention comprises the following components in parts by weight: 59 to 90 parts of polypropylene resin, 5 to 15 parts of high-density polyethylene resin, 5 to 10 parts of 1-octene-ethylene block copolymer, 5 to 10 parts of ethylene-propylene copolymer, and 5 to 15 parts of glass fiber. The present invention adopts 1-octene-ethylene block copolymer and ethylene-propylene copolymer to improve the bending and cracking resistance of the glass fiber reinforced polypropylene composite resin; at the same time, adding high-density polyethylene resin can make the glass fiber dispersed evenly in the polypropylene resin, so that the polypropylene composite material has a good appearance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of vehicle interior and exterior decoration materials, and specifically relates to a polypropylene composite material and a preparation method and application thereof. Background Art

[0002] Polypropylene has a light density, a wide range of sources, a low price, and lower carbon emissions than other materials. It is widely used in automotive interior and exterior decoration and functional parts. In particular, with the popularity of electric vehicles in recent years, more engineering materials (PA6 / PA66 / ABS) are replaced by lighter polypropylene materials because the endurance of the vehicle is related to the weight of the vehicle.

[0003] However, compared with the above materials, polypropylene has the disadvantages of low strength, easy bending, whitening and cracking, and poor scratch resistance. Taking the current automobile interior window frame strips as an example, the original PA6-GF15 material was used, which has high bending toughness and scratch resistance. However, due to its high strength, it is difficult to assemble. At present, major OEMs have replaced PA6-GF15 materials with PP-GF25 or PP-GF15 materials. However, PP-GF materials have serious surface floating fibers, whitening and cracking when bent, and poor scratch resistance, which limits its application in automobile interiors.

[0004] Therefore, it is urgent to develop a glass fiber reinforced polypropylene material with good appearance and resistance to bending cracking and scratch resistance. Summary of the invention

[0005] The object of the present invention is to overcome the deficiencies of the prior art and provide a glass fiber reinforced polypropylene material with good appearance and resistance to bending, cracking and scratching.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] In the first aspect, the present invention provides a polypropylene composite material, comprising the following components in parts by weight: 59 to 90 parts of polypropylene resin, 5 to 15 parts of high-density polyethylene resin, 5 to 10 parts of 1-octene-ethylene block copolymer, 5 to 10 parts of ethylene-propylene copolymer, 5 to 15 parts of glass fiber, and 0.05 to 2 parts of nucleating agent.

[0008] The inventor of the present invention has found that the present invention uses 1-octene-ethylene block copolymer (OBC) and ethylene-propylene copolymer (POE) as a toughening agent, which can make the glass fiber reinforced polypropylene composite resin have high rigidity and toughness at the same time, thereby improving its bending and cracking resistance performance; adding high-density polyethylene resin at the same time can improve the compatibility between the components, make the glass fiber dispersed evenly in the polypropylene resin, and make the polypropylene composite material have a good appearance, effectively avoiding the problem of glass fiber agglomeration and poor appearance in the resin due to the large difference in rheological properties between the polypropylene resin and the composite toughening agent. When the amount of 1-octene-ethylene block copolymer is large, the surface hardness of the parts will be reduced, the ability to resist external inspection damage will be reduced, and the scratch resistance will be reduced; when the amount of 1-octene-ethylene block copolymer is small, the toughness of the material system will be reduced, and the parts will be prone to bending and cracking.

[0009] As a preferred embodiment of the polypropylene composite material of the present invention, the mass ratio of 1-octene-ethylene block copolymer to ethylene-propylene copolymer is 1-octene-ethylene block copolymer:ethylene-propylene copolymer=1:1-1:2.

[0010] The inventors of the present invention have found that when the mass ratio of OBC to POE in the present invention is within the above range, the polypropylene composite material can have a more excellent bending and cracking resistance, and POE can give the polypropylene composite material a higher toughness. After compounding with a specific OBC, the OBC material has good resilience, so that the surface of the material can be partially restored after external damage, thereby improving the scratch resistance of the part.

[0011] As a preferred embodiment of the polypropylene composite material of the present invention, the melt flow rate of the 1-octene-ethylene block copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 0.5 to 44 g / 10 min; the melt flow rate of the ethylene-propylene copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 1.3 to 21 g / 10 min.

[0012] As a more preferred embodiment of the polypropylene composite material of the present invention, the melt flow rate of the 1-octene-ethylene block copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 1 to 30 g / 10 min; the melt flow rate of the ethylene-propylene copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 3.6 to 18 g / 10 min.

[0013] The inventors of the present invention have found that the present invention uses 1-octene-ethylene block copolymer and ethylene-propylene copolymer with specific melt flow rate for compounding, and compounding with specific high-density polyethylene at the same time, on the one hand, it can improve the dispersibility of glass fiber in polypropylene resin, so that the composite material has a good appearance; on the other hand, the 1-octene-ethylene block copolymer and ethylene-propylene copolymer are compounded, and within a specific fluidity range, the two types of elastomers can be pulled against each other and present a highly stretched state in the polypropylene matrix, thereby improving the toughness of the polypropylene composite material and making it have better resistance to bending and cracking.

[0014] As a preferred embodiment of the polypropylene composite material of the present invention, the nucleating agent includes at least one of acetylene carbon black, metal phosphate nucleating agents, and substituted aromatic phosphate ester nucleating agents.

[0015] The inventors of the present invention conducted experimental studies on a large number of nucleating agents and found that the use of the above-mentioned nucleating agent of the present invention is beneficial to improving the crystallization temperature and crystallinity of the composite material, enhancing the rigidity of the surface of the polypropylene composite material, thereby making it have better scratch resistance.

[0016] As a more preferred embodiment of the polypropylene composite material of the present invention, the nucleating agent includes acetylene black, metal phosphate nucleating agent, and substituted aromatic phosphate nucleating agent; the mass ratio of the acetylene black, metal phosphate nucleating agent, and substituted aromatic phosphate nucleating agent is (0.5-1.5):(0.05-0.5):(0.005-0.5).

[0017] The inventors of the present invention have found that the present invention uses the above-mentioned specific nucleating agents for compounding, wherein acetylene carbon black and phosphate metal salt nucleating agents can improve the crystallinity and crystallization rate of the material, thereby improving the rigidity of the material, especially significantly improving the surface hardness of the material, thereby improving the scratch resistance of the material; and substituted aromatic phosphate ester nucleating agents can significantly improve the toughness of the material without reducing the rigidity of the material, thereby improving the bending resistance of the material. The present invention uses three specific nucleating agents to work together to synergistically improve the bending resistance and scratch resistance of glass fiber reinforced polypropylene materials.

[0018] As the most preferred embodiment of the polypropylene composite material of the present invention, the mass ratio of the acetylene black, the metal phosphate nucleating agent, and the substituted aromatic phosphate nucleating agent is (0.5-1):(0.275-0.5):(0.005-0.2).

[0019] The inventors have found through a large number of experiments that when the mass ratio of the nucleating agent of the present invention is within the above preferred range, the final glass fiber reinforced polypropylene material can have better bending resistance and scratch resistance.

[0020] As a preferred embodiment of the polypropylene composite material of the present invention, the average length of the glass fiber is 3.0 to 4.5 mm, and the diameter of the glass fiber is 10 to 15 μm.

[0021] As a more preferred embodiment of the polypropylene composite material of the present invention, the average length of the glass fiber is 4.5 mm, and the diameter of the glass fiber is 13 μm.

[0022] The inventors of the present invention have found that the use of glass fibers with the above-mentioned average length and diameter can enable the material to maintain a certain rigidity, resist external forces during bending, and reduce the risk of bending and cracking; at the same time, appropriate length and diameter can make the glass fibers evenly distributed on the surface of the material, increase the surface hardness of the material, thereby making the composite material have better resistance to bending, cracking and scratching.

[0023] As a preferred embodiment of the polypropylene composite material of the present invention, it includes at least one of the following (I) to (II):

[0024] (I) The high-density polyethylene resin has a melt flow rate of 0.35-30 g / 10 min and a density of 0.951-0.956 g / cm2 as measured at 190°C and 2.16 kg weight according to ISO 1133-2011. 3 ;

[0025] (II) The polypropylene resin comprises at least one of homopolypropylene and copolymer polypropylene; the melt flow rate of the polypropylene resin measured at 230° C. and 2.16 kg weight according to ISO 1133-2011 is 0.4 to 50 g / 10 min.

[0026] The inventors of the present invention have found that the high-density polyethylene with the above-mentioned specific density and melt flow rate of the present invention has better flexibility, making the polypropylene composite material easier to distribute on the surface of the material during the injection molding process, thereby achieving the effect of improving the appearance.

[0027] As a more preferred embodiment of the polypropylene composite material of the present invention, the melt flow rate of the high-density polyethylene resin measured at 190°C and 2.16kg weight according to ISO 1133-2011 is 0.7-20g / 10min; the inventors have found through extensive research that the melt flow rate of the high-density polyethylene resin has the best flexibility within this preferred range, so that the prepared polypropylene composite material will not turn white or crack at the bending angle of 120°, and the scratch resistance is ≤0.5.

[0028] As a preferred embodiment of the polypropylene composite material of the present invention, the primary antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; and the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl)phosphite.

[0029] As a preferred embodiment of the polypropylene composite material of the present invention, the compatibilizer is maleic anhydride grafted polypropylene.

[0030] In a second aspect, the present invention also provides a method for preparing the above-mentioned polypropylene composite material, comprising the following steps:

[0031] S1, weighing the components in the polypropylene composite material in proportion, mixing them evenly to obtain a premix;

[0032] S2, melt-extrude and granulate the premixed material in step S1 to obtain the polypropylene composite material.

[0033] As a preferred embodiment of the preparation method of the present invention, the process parameters of the melt extrusion are: the temperature of zone 1 is 80°C, the temperature of zone 2 is 190°C, the temperature of zone 3 is 190°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 190°C, the temperature of zone 6 is 190°C, the temperature of zone 7 is 190°C, the temperature of zone 8 is 190°C, the temperature of zone 9 is 190°C, and the speed of the main engine is 450 rpm.

[0034] In a third aspect, the present invention also provides the use of the above-mentioned polypropylene composite material in the preparation of automotive decorative materials.

[0035] The inventors of the present invention have found through research that the polypropylene composite material of the present invention has good appearance, excellent scratch resistance and bending crack resistance, can be used to prepare automotive decorative materials, and has good application prospects.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention adopts a compound of 1-octene-ethylene block copolymer and ethylene-propylene copolymer as a toughening agent, which can make the glass fiber reinforced polypropylene composite resin have high rigidity and toughness at the same time, thereby improving its bending crack resistance performance; at the same time, adding the high-density polyethylene resin of the present invention can improve the compatibility between the components, make the glass fiber dispersed evenly in the polypropylene resin, and make the polypropylene composite material have a good appearance, effectively avoiding the problem of glass fiber agglomeration and poor appearance in the resin caused by the large difference in rheological properties between the polypropylene resin and the toughening agent;

[0038] (2) The present invention uses 1-octene-ethylene block copolymer and ethylene-propylene copolymer with specific melt flow rate for compounding, and compounding with specific high-density polyethylene at the same time, which can improve the dispersibility of glass fiber in polypropylene resin, so that the composite material has a more excellent appearance; on the other hand, it can improve the toughness of the polypropylene composite material, so that it has better resistance to bending cracking;

[0039] (3) The present invention uses specific nucleating agents in a specific ratio, wherein acetylene carbon black and metal phosphate nucleating agents can improve the crystallinity and crystallization rate of the material, thereby improving the rigidity of the material, especially significantly improving the surface hardness of the material, thereby improving the scratch resistance of the material; and substituted aromatic phosphate nucleating agents can significantly improve the toughness of the material without reducing the rigidity of the material, thereby improving the bending resistance of the material. The present invention uses the above three specific nucleating agents to work together to synergistically improve the bending resistance and scratch resistance of glass fiber reinforced polypropylene materials. DETAILED DESCRIPTION

[0040] The technical scheme of the present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The methods or operations used in the embodiments, unless otherwise specified, are conventional methods or conventional operations in the art.

[0041] In the examples and comparative examples of the present invention, the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial sources. The primary antioxidants used in the following examples and comparative examples of the present invention are all commercially available pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, the auxiliary antioxidants are all commercially available tris(2,4-di-tert-butylphenyl)phosphite; the compatibilizers are all commercially available maleic anhydride grafted polypropylene, and the melt flow rate is 20 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0042] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0043] Polypropylene resin 1 (PP1): PP B8101, Yanshan Petrochemical, melt flow rate is 0.4 g / 10 min (test conditions are 230°C, 2.16 kg, ISO 1133-2011).

[0044] Polypropylene resin 2 (PP2): PP EP548R, CNOOC Shell, melt flow rate is 30 g / 10 min (test conditions are 230° C., 2.16 kg, ISO 1133-2011).

[0045] Polypropylene resin 3 (PP3): PP EP5075X, Sinopec, melt flow rate 50 g / 10 min (test conditions are 230° C., 2.16 kg, ISO 1133-2011).

[0046] High-density polyethylene resin 1 (HDPE1): HDPE HYA600, ExxonMobil, melt flow rate 0.35 g / 10 min (test conditions 190 ° C, 2.16 kg, ISO 1133-2011), density 0.954 g / cm 3 .

[0047] High-density polyethylene resin 2 (HDPE2): HDPE 5000S, Daqing Petrochemical, melt flow rate 0.7 g / 10 min (test conditions 190 ° C, 2.16 kg, ISO 1133-2011), density 0.951 g / cm 3 .

[0048] High-density polyethylene resin 3 (HDPE3): HDPE 5421B, CNOOC Shell, melt flow rate 10g / 10min (test conditions 190℃, 2.16kg, ISO 1133-2011), density 0.953g / cm 3 .

[0049] High-density polyethylene resin 4 (HDPE4): HDPE HMA016, ExxonMobil, melt flow rate 20g / 10min (test conditions 190℃, 2.16kg, ISO 1133-2011), density 0.956g / cm 3 .

[0050] High-density polyethylene resin 5 (HDPE5): HDPE HMA018, ExxonMobil, melt flow rate 30g / 10min (test conditions are 190℃, 2.16kg, ISO 1133-2011), density 0.954g / cm 3 .

[0051] Low-density polyethylene resin: LDPE2426K, Maoming Petrochemical, melt flow rate is 4g / 10min (test conditions are 190℃, 2.16kg, ISO 1133-2011), density is 0.926g / cm 3 .

[0052] 1-Octene-ethylene block copolymer 1 (OBC1): INFUSE OBC 9010, Dow Chemical, melt flow rate of 0.5 g / 10 min (test conditions: 190° C., 2.16 kg, ISO 1133-2011).

[0053] 1-Octene-ethylene block copolymer 2 (OBC2): INFUSE OBC 9107, Dow Chemical, melt flow rate of 1 g / 10 min (test conditions: 190° C., 2.16 kg, ISO 1133-2011).

[0054] 1-Octene-ethylene block copolymer 3 (OBC3): INFUSE OBC 9807, Dow Chemical, melt flow rate of 15 g / 10 min (test conditions: 190° C., 2.16 kg, ISO 1133-2011).

[0055] 1-Octene-ethylene block copolymer 4 (OBC4): INFUSE OBC 9900, Dow Chemical, melt flow rate 30 g / 10 min (test conditions: 190° C., 2.16 kg, ISO 1133-2011).

[0056] 1-Octene-ethylene block copolymer 5 (OBC5): INFUSE OBC 10510, melt flow rate 44 g / 10 min (test conditions: 190° C., 2.16 kg, ISO 1133-2011).

[0057] Ethylene-propylene copolymer 1 (POE1): Vistamaxx POP 7010FL, ExxonMobil, melt flow rate of 1.3 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0058] Ethylene-propylene copolymer 2 (POE2): Vistamaxx POP 3980FL, ExxonMobil, melt flow rate 3.6 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0059] Ethylene-propylene copolymer 3 (POE3): Vistamaxx POP 6202, ExxonMobil, melt flow rate 9 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0060] Ethylene-propylene copolymer 4 (POE4): Vistamaxx POP 7050BF, ExxonMobil, melt flow rate of 18 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0061] Ethylene-propylene copolymer 5 (POE5): Vistamaxx POP 6502, ExxonMobil, melt flow rate 21 g / 10 min (test conditions are 190° C., 2.16 kg, ISO 1133-2011).

[0062] Acetylene black: Acetylene black DENKA BLACK, Shanghai Zhongrong.

[0063] Phosphate metal salt nucleating agent 1: Nucleating agent NP-509, Beijing Jihaichuan Technology Development Co., Ltd.

[0064] Phosphate metal salt nucleating agent 2: NAA-325. Guangzhou Chenghe Technology Co., Ltd.

[0065] Substituted aryl phosphate nucleating agent 1: TMP-5, Shanxi Chemical Research Institute.

[0066] Substituted aryl phosphate nucleating agent 2: TMB-5, Shanxi Chemical Research Institute.

[0067] Polyolefin β-crystal nucleating agent: NB-328, Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.

[0068] Glass fiber: ECS13-4.5-508A, Jushi glass fiber, average length 4.5mm, diameter 13μm.

[0069] Examples 1 to 24 and Comparative Examples 1 to 12

[0070] Examples 1 to 24 and Comparative Examples 1 to 12 are polypropylene composite materials of the present invention. The components and weight proportions of the polypropylene composite materials of Examples 1 to 24 and Comparative Examples 1 to 12 are shown in Tables 1 to 5.

[0071] The preparation method of the polypropylene composite material of Examples 1 to 24 and Comparative Examples 1 to 12 comprises the following steps:

[0072] S1, weighing the components in the polypropylene composite material in proportion, mixing them evenly to obtain a premix;

[0073] S2. Place the premixed material in step S1 into a twin-screw extruder for melt extrusion and granulation drying to obtain the polypropylene composite material; the process parameters of the melt extrusion are: the temperature of zone 1 is 80°C, the temperature of zone 2 is 190°C, the temperature of zone 3 is 190°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 190°C, the temperature of zone 6 is 190°C, the temperature of zone 7 is 190°C, the temperature of zone 8 is 190°C, the temperature of zone 9 is 190°C, and the rotation speed of the main engine is 450 rpm; the aspect ratio of the twin-screw extruder is 48:1.

[0074] Table 1 Weight parts: parts

[0075]

[0076]

[0077] Table 2 Weight parts: parts

[0078]

[0079]

[0080] Table 3 Weight parts: parts

[0081]

[0082] Table 4 Weight parts: parts

[0083]

[0084]

[0085] Table 5 Weight parts: parts

[0086]

[0087]

[0088] Effect example

[0089] The polypropylene composite materials of Examples 1 to 24 and Comparative Examples 1 to 12 were respectively made into 100mm*100m*3mm square plates and Volkswagen K31 leather grain plates for judging the appearance; the polypropylene composite materials of Examples 1 to 24 and Comparative Examples 1 to 12 were prepared into ISO standard 1A type tensile test strips for judging the bending whitening performance; the polypropylene composite materials of Examples 1 to 24 and Comparative Examples 1 to 12 were prepared into Volkswagen K31 leather grain for judging the scratch resistance of the material. The test method is as follows:

[0090] (1) Appearance grade

[0091] Test method: visual inspection;

[0092] Evaluation criteria: (1) Grade A: no floating fibers on the surface of the smooth board, no floating fibers on the K31 leather grain board; (2) Grade B: a small amount of floating fibers can be seen on the surface of the smooth board, no floating fibers can be seen on the K31 leather grain board; (3) Grade C: obvious floating fibers can be seen on the surface of the smooth board, a small amount of floating fibers can be seen on the K31 leather grain board;

[0093] Performance requirements: Appearance grade ≥ B.

[0094] (2) Bending crack resistance

[0095] Test method: Bend the ISO standard 1A specimen at both ends to 45 degrees, 90°C, and 120°C, and observe whether there are cracks or whitening problems at the bends;

[0096] Performance requirements: Bending angle ≥ 90°, no cracking or whitening at the bending point.

[0097] (3) Scratch resistance

[0098] Test method: Adopt Volkswagen Group PV3974 standard, use 3N weight, scratch a hair = 16.0mm disc, contact radius is 0.5mm, draw 80 parallel marks on the surface of the sample, and judge the gloss change of the scratched part is ≤0.6;

[0099] Performance requirements: The standard requires that the glossiness before and after scratching DGG ≤ 0.6.

[0100] The test results are shown in Tables 6 and 7 below.

[0101] Table 6

[0102]

[0103]

[0104] Table 7

[0105]

[0106] It can be seen from Tables 6 to 7 that when the technical solution of the present invention is adopted, the obtained products have good appearance, excellent bending crack resistance and scratch resistance, and the appearance grade can reach B or above. When the bending angle is ≥90°, there is no cracking or whitening at the bending part of the product, and the scratch resistance is ≤0.6.

[0107] Comparison of Examples 1 to 9 and Comparative Examples 1 to 2 shows that the melt flow rates of 1-octene-ethylene block copolymer and ethylene-propylene copolymer have a significant effect on the appearance, bending resistance and scratch resistance of the product. When the melt flow rate of 1-octene-ethylene block copolymer is 1-30 g / 10 min (190°C, 2.16 kg weight conditions, ISO 1133-2011), the appearance grade of the polypropylene composite material reaches Class A, and when the bending resistance angle can reach 120°, there is no cracking and whitening at the bending. At the same time, when the melt flow rate of ethylene-propylene copolymer is 3.6 to 18 g / 10 min (190°C, 2.16 kg weight conditions, ISO 1133-2011), the comprehensive performance of the obtained polypropylene composite material is more excellent.

[0108] By comparing Example 3, Examples 10 to 12 and Comparative Examples 3 to 4, it can be seen that when the mass ratio of 1-octene-ethylene block copolymer to ethylene-propylene copolymer is 1:1 to 1:2, the appearance grade of the polypropylene composite material can reach Grade A, and has better appearance performance.

[0109] Comparing Example 3, Examples 13 to 16 and Comparative Examples 5 to 6, it can be seen that the nucleating agent is compounded with acetylene carbon black, metal phosphate nucleating agent and substituted aryl phosphate nucleating agent according to a specific ratio, and the obtained polypropylene composite material has excellent scratch resistance, which can well improve the surface rigidity of the polypropylene composite material, thereby having more excellent scratch resistance; especially the polypropylene composite material obtained in Example 3, Example 13 and Example 14 has better bending resistance, and no cracking and whitening occurs at the bending point when the bending angle reaches 120°. Comparing Example 3 and Example 17, it can be seen that the substituted aryl phosphate nucleating agent of the present invention is compounded with acetylene carbon black and metal phosphate nucleating agent, which has more excellent scratch resistance. Comparing Example 3 and Comparative Examples 7 and 8, it can be seen that not adding a nucleating agent or adding more nucleating agents will lead to a decrease in the bending resistance and scratch resistance of the polypropylene composite material.

[0110] By comparing Example 3, Examples 18-21 and Comparative Example 10, it can be seen that when the melt flow rate (190°C, 2.16 kg weight conditions, ISO 1133-2011) of the high-density polyethylene resin is 0.7-20 g / 10 min, the prepared polypropylene composite material does not show whitening and cracking at the bending angle of 120°, and the scratch resistance is ≤0.5; by comparing Example 3 and Comparative Example 9, it can be seen that compared with the low-density polyethylene resin, the high-density polyethylene resin of the present invention can make the appearance of the polypropylene composite material reach Class A, and has more excellent bending crack resistance and scratch resistance.

[0111] By comparing Example 3 and Comparative Examples 11-12, it can be seen that when the weight portion of the high-density polyethylene resin is 5 to 15 parts, the appearance performance of the polypropylene composite material reaches Class A, and the scratch resistance is 0.3, having a good appearance and better scratch resistance.

[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polypropylene composite material, characterized in that: The invention comprises the following components in parts by weight: 59-90 parts of polypropylene resin, 5-15 parts of high-density polyethylene resin, 5-10 parts of 1-octene-ethylene block copolymer, 5-10 parts of ethylene-propylene copolymer, 5-15 parts of glass fiber, and 0.05-2 parts of nucleating agent; The melt flow rate of the 1-octene-ethylene block copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 0.5-44 g / 10 min; the melt flow rate of the ethylene-propylene copolymer measured at 190°C and 2.16 kg weight according to ISO 1133-2011 is 1.3-21 g / 10 min; the melt flow rate of the high-density polyethylene resin measured at 190°C and 2.16 kg weight according to ISO1133-2011 is 0.35-30 g / 10 min, and the density is 0.951-0.956 g / cm 3 ; The nucleating agent includes acetylene black, metal phosphate nucleating agent, and substituted aromatic phosphate nucleating agent.

2. The polypropylene composite material according to claim 1, characterized in that The mass ratio of the 1-octene-ethylene block copolymer to the ethylene-propylene copolymer is 1-octene-ethylene block copolymer:ethylene-propylene copolymer=1:1-1:

2.

3. The polypropylene composite material according to claim 1, characterized in that: The mass ratio of the acetylene carbon black, the metal phosphate nucleating agent, and the substituted aromatic phosphate nucleating agent is (0.5-1.5):(0.05-0.5):(0.005-0.5).

4. The polypropylene composite material according to claim 1, characterized in that: The average length of the glass fiber is 3.0-4.5 mm, and the diameter of the glass fiber is 10-15 μm.

5. The polypropylene composite material according to claim 1, characterized in that: The polypropylene resin includes at least one of homopolymer polypropylene and copolymer polypropylene; the melt flow rate of the polypropylene resin is 0.4-50g / 10min under the conditions of 230°C and 2.16kg weight according to ISO 1133-2011.

6. The polypropylene composite material according to claim 1, characterized in that: The invention also comprises the following components in parts by weight: 0.05-0.5 parts of a main antioxidant, 0.05-0.5 parts of an auxiliary antioxidant, and 0.5-5 parts of a compatibilizer.

7. The method for preparing the polypropylene composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, weighing the components for preparing the polypropylene composite material according to proportion, mixing them evenly to obtain a premix; S2, melt-extrude the premixed material in step S1, granulate and dry to obtain the polypropylene composite material.

8. Use of the polypropylene composite material according to any one of claims 1 to 6 in the preparation of automotive interior or exterior materials.

Citation Information

Patent Citations

  • Low-gloss, good-appearance and high-impact glass fiber reinforced polypropylene material

    CN112457588A

  • High-fluidity and high-gloss polypropylene composition and preparation method thereof

    CN112745625A